2021
DOI: 10.1016/j.neurop.2021.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Repercusión de la pandemia por COVID-19 en la formación de los residentes de neurología españoles

Abstract: Introducción La pandemia ocasionada por la aparición del SARS-CoV-2, ha transformado la práctica médica, y ha alterado gravemente la formación de los médicos residentes a nivel mundial. Desde la Sociedad Española de Neurología (SEN) se ha querido conocer el grado de repercusión que la COVID-19 ha tenido en el ámbito formativo entre los residentes de neurología. Método Se realizó un estudio descriptivo transversal mediante el envío de una encuesta por email… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
2
2
0
1
Order By: Relevance
“…During the early waves of the pandemic, learning environments were severely affected and deteriorated, consistent with ndings from studies conducted in Spain and other countries in our region [47,48,53,54].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…During the early waves of the pandemic, learning environments were severely affected and deteriorated, consistent with ndings from studies conducted in Spain and other countries in our region [47,48,53,54].…”
Section: Discussionsupporting
confidence: 90%
“…This reassignment to different services affected family and community medicine residents more than other specialties because of their more transversal and multidisciplinary training, allowing them to perform professionally in primary care centers, hospitals, and out-of-hospital.emergency services. All of this was associated with an increase in work hours, which resulted in less time dedicated to specialty training, similar to what has been described in other studies [47,49,50], but other studies conducted in the United States reported a decrease in face-to-face working hours in some specialties [51], which in some cases was partially compensated by an increase in the number of hours worked from home [52].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Pero en esta pandemia y con la restricción de "no salir de casa", ¿cómo se está intentando lograr la formación práctica de los futuros profesionales? Como docentes de instituciones universitarias conocemos las vicisitudes por las que han transcurrido las disciplinas más aplicadas como la psicología(Pereyra et al, 2020) la medicina(Cerdán et al, 2021), la enfermería(Meléndez Chávez et al, 2020; Orozco-López, 2021), las ingenierías(Aranda et al, 2020; Sánchez y Ariza, 2020;Guarnizo, 2021), y las ciencias del deporte(Nahuelpi et al, 2021;Araujo, 2020).…”
unclassified